PENGARUH PROFITABILITAS, LIKUIDITAS, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN DENGAN STRUKTUR MODAL SEBAGAI VARIABEL MODERASI - Yusuf Rahmatullah; Andy Dwi Bayu Bawono (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to analyze the influence of profitability, liquidity, and firm size on firm value, with capital structure as a moderating variable, on property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2021–2023. The research sample was obtained using purposive sampling technique, with a final total of 61 companies that met the criteria. The analysis method used is multiple linear regression. The research results indicate that profitability and liquidity do not have a significant effect on firm value, whereas firm size has a significant negative effect. Additionally, capital structure does not moderate the relationship between profitability and liquidity on firm value, but it does moderate the relationship between firm size and firm value with a significant negative influence.